2019
DOI: 10.15406/ppij.2019.07.00235
|View full text |Cite
|
Sign up to set email alerts
|

Natural Foods and Indian herbs of cardiovascular interest

Abstract: Since the start of human development, herbs have been an essential piece of society, esteemed for both their culinary and medicinal properties. Cardiovascular malady is the main executioner in the United States. Diet and way of life assume an imperative job in avoiding and switching heart infection, and certain herbs and supplements can help in bringing down hazard for heart ailment and treat heart conditions. Contrasted and customary prescriptions, herbal drugs don't require clinical investigations previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 171 publications
(139 reference statements)
0
7
0
Order By: Relevance
“…Additionally, BP can remain poorly controlled despite up to six physician visits per year. 86 Across South Asia, overall hypertension prevalence is estimated to be 27%. Prospective Urban Rural Epidemiology study has shown more than 50% are unaware of it and up to 80% of hypertensive patients have low adherence to medication.…”
Section: Cvd Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, BP can remain poorly controlled despite up to six physician visits per year. 86 Across South Asia, overall hypertension prevalence is estimated to be 27%. Prospective Urban Rural Epidemiology study has shown more than 50% are unaware of it and up to 80% of hypertensive patients have low adherence to medication.…”
Section: Cvd Preventionmentioning
confidence: 99%
“…94 Pharmacist intervention can increase patients' knowledge about their condition in a way that positively modifies their beliefs about medicines, increased medication intensification without significant change in medication adherence, modify factors affecting adherence, improve adherence and patient QoL by reducing BP levels in patients treated with antihypertensive agents, increased referral acceptance. 86,[95][96][97][98][99] Interventions that were most effective included combinations of more convenient care, information, reminders, self-monitoring, reinforcement, counseling, family therapy, psychological therapy, crisis intervention, manual telephone follow-up, and supportive care. 83 Weight loss has been noted to modify risk factors via improving insulin sensitivity, reducing inflammation, decreasing blood pressure and modifying the lipid profile.…”
Section: Cvd Preventionmentioning
confidence: 99%
“…BP is still uncontrolled in 50% of the US population with hypertension. Additionally, BP can remain poorly controlled despite up to six physician visits per year [86]. Across South Asia, overall hypertension prevalence is estimated to be 27%.…”
Section: Cvd Preventionmentioning
confidence: 99%
“…Pharmacist intervention can increase patients' knowledge about their condition in a way that positively modifies their beliefs about medicines, increased medication intensification without significant change in medication adherence, modify factors affecting adherence, improve adherence and patient QoL by reducing BP levels in patients treated with antihypertensive agents, increased referral acceptance [86], [95][96][97][98][99]. Interventions that were most effective included combinations of more convenient care, information, reminders, self-monitoring, reinforcement, advocacy, family therapy, psychotherapy, crisis intercession, regular telephone follow-up, and supportive care [83].…”
Section: Cvd Preventionmentioning
confidence: 99%
“…Therefore, it is feasible that the close interaction between ROS and calcium in inducing cell death can be endowed with therapeutic implications (Münzel et al, 2017). Interestingly, there are many natural products that can simultaneously reduce calcium overload and ROS over-production, exerting cardiovascular protective, and HF-preventing effects (Jiang et al, 2016;Mohiuddin, 2019). Flavones including isoflavones, which are one of the most abundant components in plants and fruits, have been intensely studied and applied in markets as a dietary supplement to prevent the incidence of heart diseases including HF (Dixon and Pasinetti, 2010;McCullough et al, 2012;Zamora-Ros et al, 2013).…”
Section: Introductionmentioning
confidence: 99%